An analysis of women victims of sexual violence in one area in Republic of Korea - Gyeong-Eun Heo; Jae Hong Sang; Tae-Hee Kim; Hae-Hyeog Lee (IMR Press, 2022)
Background: This study analyzed the characteristics of sexual violence against women that occurred in one area in Republic of Korea. Methods: The medical records of 332 women who visited Emergency Unit, tertiary university Hospital with sexual violence as main complaint from Jun. 2007 to Oct. 2016 and were examined by obstetricians and gynecologists were reviewed retrospectively. Results: Most of victims were in their 20s. 79.5% of victims had sexual experience before case and this rate in adolescent group aged from 13 to 20 was 65.2%. 52.1% of cases occurred under influence of alcohol and 52.1% of victims had hepatitis B antibody. The most frequent condition of sexual violence in the age group of victims over 13 years old were Jun.-Aug., 0:00-6:00, stranger, and accommodation facility. Those conditions in victims under 13 years old were Sep.-Nov., 12:00-18:00, outdoor, and acquaintance. The follow-up rate after examination was performed in 40.1% of victims. Conclusions: This study showed that sexual violence against child has different characteristics with that general sexual violence. The low rate of carrying hepatitis B antibody in victims indicated the importance of vaccine inoculation and further studies are recommended to obtain statistical significance of the results in this study.